Kroket Past and Present Culinary Modifications and Innovations of The People of Palu City - Triawati, Komang (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Ampat Yogyakarta, 2022)
Culinary has mushroomed in almost every area, including Palu City, which is dubbed the City by the local community, having snacks using sweet potatoes as the main ingredient for making croquettes with vegetable ragout filling from carrots, sweet potatoes and sprouts, which are Palu croquettes. Kroket has various names that differ in each country, as France is called (croquet)crispy, while the Netherlands is called Kroketten. Bitterballen is made from meat ragout, cheese mixed with sauce and seafood. One of the famous croquette restaurants in Amsterdam Is Van Dobben and hotlkmp Pattiserie, both o which are renowned for Dutch croquettes. From its history, croquettes can now be found in almost all of Indonesia, one of which is the city of Palu. After the croquette is implemented in hot oil, it is like a rocket that can fly from the bottom to the top by looking at the foam on the fried croquettes because the croquettes have been sprinkled with egg white producing the froth of the croquettes themselves. The modification of the main ingredient of potato is changed to sweet potato so that the lower class people can consume croquettes instead of using potato as the primary ingredient, which is a little more expensive than a sweet potato. From here, culinary lovers modify and innovate to change the main ingredients to still make croquettes with a taste and texture that is soft, sweet, savoury, crunchy and coated with a sprinkling of bread and then fried golden. This one dish can be found every day at the Kori shop located on Jalan Attorney General Huntap 1 Tondo, making this one of the most popular snacks the people of Palu City enjoy.